The economy of Pakistan - Andrus, J. Russell; Mohammed, Azizali F. (Stanford, Calif. : Stanford University Press, 1958)
The study represents an attempt to discuss main aspects of Pakistan's economy.
Includes bibliographical footnotes and index.
kjo 18/01/2019
Loans
Keywords: Economics; Pakistan